Analisis Sistem Akuntansi Pertanggungjawaban Uang Perjalanan Dinas Di Setdakab Nagan Raya - Dina Fitriansyah; Ika Rahmadani (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2023)
This research aims to analyze the Accountability of Business Travel money in SETDAKAB Nagan Raya and whether it has been prepared by Minister of Finance Regulation No. 07/PMK.05/2008 concerning the Second Amendment to the Regulation of the Minister of Finance Number 45/PMK. 05/2007, which contains official domestic travel for state officials, civil servants, and non-permanent employees. The research method used in this research is a descriptive qualitative method by observing work practices at research locations to obtain primary and secondary data. The data was recorded and collected using interview techniques with Expenditure Treasurers, Assistant Treasurers, and SPPD operators to see the mechanism of the administration process for official travel money accountability. The results of this study also show that the budget for travel in the Nagan Raya region from 2018 to 2020 has experienced an increase in funding, and in 2021 there was a decrease in the budget due to budget cuts. The budget has been allocated to help residents affected by the pandemic. It has been effective and efficient in carrying out the payment of official travel money at SETDAKAB Nagan Raya.